Stone vessels and values in the Bronze age Mediterranean - Bevan, Andrew 1974- (Cambridge University Press, 2007)
The societies that developed in the eastern Mediterranean during the Bronze Age produced the most prolific and diverse range of stone vessel traditions known at any time or anywhere in the world. Stone vessels are therefore a key class of artefact in the early history of this region. As a form of archaeological evidence, they offer important analytical advantages over other artefact types - virtual indestructibility, a wide range of functions and values, huge variety in manufacturing traditions, as well as the subtractive character of stone and its rich potential for geological provenancing. In this 2007 book, Andrew Bevan considers individual stone vessel industries in great detail. He also offers a highly comparative and value-led perspective on production, consumption and exchange logics throughout the eastern Mediterranean over a period of two millennia during the Bronze Age (ca.3000–1200 BC)